Two subtypes of compulsive sexual behavior disorder - Golder, Sarah; Markert, Charlotte; Psarros, Rhea; Discher, Julian Peter; Walter, Bertram; Stark, Rudolf (Frontiers in Psychiatry, 2023)
Models explaining addictive behaviors such as the Interaction of Person-Affect-Cognition-Execution (I-PACE) model emphasize the importance of reinforcement mechanisms for developing and maintaining these behaviors, including compulsive sexual behavior disorder (CSBD) as well as personal characteristics as vulnerability factors. This study aimed to determine whether there are CSBD subtypes distinguished by reinforcement sensitivity. We hypothesize that one subtype is sensitive to positive reinforcement (C+subtype) and one is sensitive to negative reinforcement (Ȼ-subtype). We calculated a cluster analysis with data from 62 patients with CSBD and tested differences between the identified clusters by t-test. The sample consisted only of men. Cluster variables were: the sensitivity to the Behavioral Inhibition and Approach System (BIS/BAS), the severity of depressive symptoms (BDI-II), the severity of Trait Anxiety (STAI-T), Sexual Sensation Seeking (SSSS), Thrill- and Adventure Seeking (SSS-V subscale), Disinhibition (SSS-V subscale), Experience Seeking (SSS-V subscale), and Boredom Susceptibility (SSS-V subscale). Between-cluster differences were analyzed for Trait Sexual Motivation (TSMQ) and Sexual Compulsivity (SCS). The results showed a two-cluster solution with cluster 1 representing patients sensitive to negative reinforcement (Ȼ-subtype) and cluster 2 representing patients sensitive to positive reinforcement (C+subtype). No significant difference in symptom severity of Sexual Compulsivity between clusters was found. Cluster 2 showed higher Importance of Sex and a higher motivation to seek sexual encounters than cluster 2. We found a two-cluster solution regarding reinforcement sensitivity in patients with CSBD. This may have clinical implications regarding individual therapy by focusing on the underlying maintenance mechanisms.